The development trend of music art based on content analysis method - Jiao, Pengcheng (Applied mathematics and nonlinear sciences, 2024)
In the Internet-mediated environment, and in the midst of the ongoing networking process, music art trends are changing accordingly. The purpose of this paper is to make an in-depth observation and reflection on this topic from a theoretical perspective. Therefore, the normalization algorithm is used as the theoretical basis to create a BN-content analysis model. Calculations show that the degree of impediment of the teaching environment to the development of row music art is 64%. And the most likely development trend of pop music is the development of pop music in the field of education, whose comprehensive development degree is 95%. This is followed by the pop music technology area, which has a combined development level of 91%. The calculation shows that music education in higher education has the highest impact with an impact factor of 1.05. This is because music education in universities and primary and secondary schools is gradually returning to the education and study of traditional Chinese music. The influence of the media sector on traditional music and art trends is 0.71. For example, the singers on the TV show “I’m a Singer” have been spreading folk music in their performances.